2012
DOI: 10.1542/peds.2010-2301
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Temperature Elevation, Epidural Use, and Adverse Outcome in Term Infants

Abstract: The proportion of infants experiencing adverse outcomes increased with the degree of epidural-related maternal temperature elevation. Epidural use without temperature elevation was not associated with any of the adverse outcomes we studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 40 publications
7
65
1
4
Order By: Relevance
“…The association found in our cohort may be related to the increased risk of fever and possible sepsis that has been observed in mothers receiving epidural anaesthesia and in their newborn (Mercer et al, 2007;Greenwell et al, 2012). Other alterations that have been associated with exposure to epidural analgesia, including respiratory depression, may also play a role (Poole, 2003;Mercer et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The association found in our cohort may be related to the increased risk of fever and possible sepsis that has been observed in mothers receiving epidural anaesthesia and in their newborn (Mercer et al, 2007;Greenwell et al, 2012). Other alterations that have been associated with exposure to epidural analgesia, including respiratory depression, may also play a role (Poole, 2003;Mercer et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
“…These have been associated with an increased heart rate and altered Apgar index and encephalopathy index values in the newborn and with convulsions during the neonatal period (Leighton and Halpern, 2002;Reynolds, 2010 However, published data on the impact of epidural analgesia have been contradictory, and this issue remains controversial among the healthcare professionals involved. Thus, some studies associated epidural analgesia with a reduced Apgar index or a delay in the early initiation of breast feeding, whereas others found no differences (Anim-Somuah et al, 2011;Greenwell et al, 2012;Jones et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Epidural analgesia is associated with intrapartum fever [7,8,9,10] and was shown to be associated with adverse neonatal [11] and maternal outcomes such as lower umbilical arterial pH and increased rate of instrumental delivery [12]. Prolonged labor is linked with intrapartum fever [13], as well as with adverse neonatal [4,5,6] and maternal outcomes [6,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Impey et al [17,18] demonstrated that intrapartum fever is associated with an almost 5-fold risk for neonatal encephalopathy and a 3.4-fold increase in the risk of unexplained neonatal seizures [17]. In a small retrospective study, neonates of febrile parturients had increased risk of low Apgar scores, seizures, hypotonia, and need for assisted ventilation [11]. …”
Section: Discussionmentioning
confidence: 99%
“…La causa más frecuente de fiebre intraparto es el uso de la anestesia epidural que es una fiebre no infecciosa [1][2][3][4][5][6][7][8][9] . Existen también otros factores de riesgo clásicos, como la primiparidad, trabajo de parto prolongado, rotura de membranas prolongada, colonización por estreptococo del grupo B. .…”
Section: Introductionunclassified